HISTORICAL OVERVIEW OF FOREIGN LANGUAGE TEACHING IN EUROPE - Avazmatova, Marhabo (Журнал иностранных языков и лингвистики, 2021)
This article considers an overview of the development in Foreign Language Teaching in Europe. Till the 16th century Latin was studied as a common foreign language, later other western languages such as English, French and Italian became popular and using the Latin language is decreased gradually and finally be a dead language. In the 18th century, utilizing the English language was increased day by day because of the economical development of the United States of America. It is common knowledge that economically strong country’s language is usually learned by other nations to do partnership with that country. Consequently, now English is considered a global language and is taught as a main foreign language in different parts of the world.